EXAMINING CONSUMER BEHAVIOR ON THE DEVELOPMENT OF GREEN HOTELS IN KAZAKHSTAN - Turginbayeva, A. N.; Shaikh, A. A.; Zhakupbekova, G. E. (Farabi Journal of Social Sciences, 2022)
International organizations, including the United Nations and member states of the European Union, are focusing on promoting green consumerism in various sectors, including the hospitality industry. The same picture is currently observed in Kazakhstan and other states of Central Asia. This article examines consumer behavior when accessing and using green hotel services based on the theory of planned behavior. Depending on the degree of knowledge of consumers, the features of their behavior in relation to the activities of a green hotel are discussed. This study provides for the study of the possibility of applying the theory of planned behavior (TPB) in the hotel business of the Republic of Kazakhstan and was developed by conducting a survey among customers of 3, 4, 5-star hotels in Almaty. The study involved 50 respondents from 3 hotels. A questionnaire was chosen as the survey instrument. Questionnaires were designed to determine the interest of hotel guests in buying environmentally friendly hotel products. The results of the study showed that, in general, there was a positive attitude of consumers towards the use of green products. Keywords: Theory of planned behavior, consumer purchase intention, sustainable products.